Blockade of MIF–CD74 Signalling on Macrophages and Dendritic Cells Restores the Antitumour Immune Response Against Metastatic Melanoma - Figueiredo, Carlos R.; Azevedo, Ricardo A.; Mousdell, Sasha; Resende-Lara, Pedro T.; Ireland, Lucy; Santos, Almudena; Girola, Natalia; Cunha, Rodrigo L. O. R.; Schmid, Michael C.; Polonelli, Luciano; Travassos, Luiz R.; Mielgo, Ainhoa (Frontiers in Immunology, 2018)
Mounting an effective immune response against cancer requires the activation of innate and adaptive immune cells. Metastatic melanoma is the most aggressive form of skin cancer. While immunotherapies have shown a remarkable success in melanoma treatment, patients develop resistance by mechanisms that include the establishment of an immune suppressive tumor microenvironment. Thus, understanding how metastatic melanoma cells suppress the immune system is vital to develop effective immunotherapies against this disease. In this study, we find that macrophages (MOs) and dendritic cells (DCs) are suppressed in metastatic melanoma and that the Ig-CDR-based peptide C36L1 is able to restore MOs and DCs’ antitumorigenic and immunogenic functions and to inhibit metastatic growth in lungs. Specifically, C36L1 treatment is able to repolarize M2-like immunosuppressive MOs into M1-like antitumorigenic MOs, and increase the number of immunogenic DCs, and activated cytotoxic T cells, while reducing the number of regulatory T cells and monocytic myeloid-derived suppressor cells in metastatic lungs. Mechanistically, we find that C36L1 directly binds to the MIF receptor CD74 which is expressed on MOs and DCs, disturbing CD74 structural dynamics and inhibiting MIF signaling on these cells. Interfering with MIF–CD74 signaling on MOs and DCs leads to a decrease in the expression of immunosuppressive factors from MOs and an increase in the capacity of DCs to activate cytotoxic T cells. Our findings suggest that interfering with MIF–CD74 immunosuppressive signaling in MOs and DCs, using peptide-based immunotherapy can restore the antitumor immune response in metastatic melanoma. Our study provides the rationale for further development of peptide-based therapies to restore the antitumor immune response in metastatic melanoma.